Multi-locational study on plant growth regulators to minimize pre-mature fruit drop and maximize postharvest quality of apples - Noosheen Zahid; Bassam F. Alowaiesh; Nasir Masood; Khawaja Shafique Ahmad; Samina Khalid; Muhammad Shafique Khalid; Mehdi Maqbool; Shahid Iqbal Awan; Zoha Imtiaz (Cogent Food & Agriculture)
Plant growth regulators (PGR’s) are considered potential substances which lessen the abiotic stresses and help in delaying the pre-mature fruit drop (PFD). Therefore, a two-year (2021 and 2022) multi-locational study was designed to assess the effects of three different PGR’s (NAA, 2, 4-D, GA3) on PFD and postharvest quality of selected apple varieties (‘Kashmir Amri’, ‘Red Delicious’, ‘Star Crimson’) grown at three different locations (Bagh, Dheerkot, Rawalakot) of Azad Jammu and Kashmir (AJK). All PGR’s were applied through foliar spray using a low pressure hand sprayer before the flowering period at the same concentration (25 ppm), while apple trees without any treatment application served as control. Apple trees sprayed with 25 ppm GA3 showed 44.56% less PFD at Dheerkot location as compared to control. Moreover, 25 ppm GA3 treated fruits showed better fruit size, fruit weight, and overall yield as well. In terms of postharvest quality parameters, a significantly high amount of strife index (5.60%), titratable acidity (2.58%), total soluble solids (13.81%), crude fiber (1.44%), total ash content (0.51%), total phenolics (136.3 mg GAE/100g FW), total flavonoids (14.83 mg/100g FW) and antioxidant activity (97.0 µg/100g FW) was found in apple trees sprayed with 25 ppm GA3 as compared with other treatments. Among apple varieties, ‘Star Crimson’ while among locations, Dheerkot showed promising results. Thus, the overall results of this study revealed that PFD could be potentially minimized and postharvest quality could be enhanced with 25 ppm GA3 spray, while Dheerkot is the most suitable location for growing apples.